Demographic-Based Assessment Of Heavy Metals In The Breastmilk Of Selected Mothers In Zamboanga City (Journal of Namibian Studies : History Politics Culture, 2022)
Mother’s milk is the best method of nutrition for infants. Breast milk also has an influence on the development of intestinal microflora and structural-functional maturity of mucous membranes and reduces the risk of allergies and autoimmune diseases. This study aimed to determine the levels of heavy metals such as Cu2+, Pb2+, Cd2+ in parts per million in the breast milk of nursing mothers, the significant difference if the levels of  Cu2+, Pb2+, and Cd2+ of the breast milk sample of mothers when grouped according to age, occupational status, number of children and tribal affiliations, and whether the level of heavy metals present exceeded the limit set by JECFA. This study used a descriptive design using the Kruskal-Wallis non-parametric test. Findings revealed that the level of concentrations of the heavy metals Cu2+ had the highest parts per million followed by Pb2+, and Cd2+ respectively. Moreover, the levels of these heavy metals do not exceed JEFCA. There was no significant difference in the level of heavy metals when nursing mothers were grouped categorically. In the light of foregoing findings and conclusions drawn from this study, it is safe to say that the breastmilk of the sampling mothers was not harmful to their children.